Genetic insights into Alpine goats raised on Lombardy’s farms - Ferrari, Carlotta; Punturiero, Chiara; Delledonne, Andrea; Milanesi, Raffaella; Bagnato, Alessandro; Strillacci, Maria Giuseppina (Frontiers in Animal Science, 2025)
This study investigates the genomic architecture of two Alpine dairy goat breeds, Camosciata delle Alpi (CAM) and Saanen (SAA), managed in ten herds located in Lombardy, northern Italy. Through medium-density SNP genotyping (GGP Goat 70K), we assessed population structure, genetic diversity, and Runs of Homozygosity (ROH) to evaluate the effects of breeding practices and herd-level management strategies on genetic variation. A total of 1,283 animals (CAM: 977; SAA: 306) were analyzed. Principal Component Analysis and ADMIXTURE results confirmed a clear genetic separation between the two breeds, with substantial intra-breed variation linked to herd-specific selection histories. ROH-based inbreeding coefficients (FROH) were moderate overall (mean FROH: 0.060 in CAM and 0.041 in SAA), though some herds displayed elevated values, suggestive of recent inbreeding or reduced gene flow. ROH analysis revealed a predominance of short segments (<2 Mb), consistent with background or historical inbreeding, and only a limited presence of long ROH (>8 Mb). Shared ROH islands on chromosomes 8, 12, and 14 were detected across both breeds and most herds, encompassing functionally relevant genes involved in thermoregulation (AQP3), fertility (RNF17), metabolic balance (ATP12A), and stress resilience. Notably, VPS13B was consistently detected in 9 out of 10 herds and in both breeds, and is known for its involvement in female fertility and skeletal traits in ruminants. Breed-specific ROH islands revealed further candidate genes: SDC1, ARHGEF17, and CAPNS2 in CAM, and DNAJA1, ATP6V0D1, UBAP1, and ZDHHC1 in SAA, related to milk production, mastitis resistance, heat stress response, and skeletal development. These findings highlight the value of integrating genomic tools into herd management. Genomic surveillance can guide sustainable selection strategies, mitigate inbreeding risks, and support the long-term genetic improvement of Alpine goat populations under diverse production systems.